Impact of Interferon-α Receptor-1 Promoter Polymorphisms on the Transcriptome of the Hepatitis B Virus-Associated Hepatocellular Carcinoma - Karamitros, Timokratis; Papatheodoridis, George; Paraskevis, Dimitrios; Hatzakis, Angelos; Mbisa, Jean L.; Georgopoulou, Urania; Klenerman, Paul; Magiorkinis, Gkikas (Frontiers in Immunology, 2018)
Background & Aims: Genetic polymorphisms within the promoter of Interferon-α Receptor type-1 (IFNAR1) have been associated with the susceptibility to and the outcome of chronic Hepatitis B Virus (HBV) infection. However, the impact of these polymorphisms in the transcriptome of the HBV-associated hepatocellular carcinoma (HCC) remains largely unexplored. Methods: Using whole-genome and exome sequencing data from The Cancer Genome Atlas (TCGA) project, we characterized three Single-Nucleotide-Polymorphisms (SNPs:-568G/C,-408C/T,-3C/T) and one Variable Number Tandem Repeat (VNTR:-77(GT)n) within the IFNΑR1 promoter sequence in 49 HCC patients. RNAseq data from 10 genotyped HCC samples were grouped according to their -77VNTR or -3SNP genotype to evaluate the impact of these polymorphisms on the differential expression on the HCC transcriptome. Results: There is a 4-fold higher impact of the -77VNTR on the HCC transcriptome compared to the -3SNP (q<0.1,p<0.001). The expression of the primary IFNAR1 transcript is not affected by these polymorphisms but a secondary, HCC-specific transcript is expressed only in homozygous -77VNTR ≤8/≤8(GT)n samples (p<0.05). At the same time, patients carrying at least one -77VNTR >8(GT) allele, presented a strong up-regulation of the Fibronectin-1 (FN1) gene, which has been associated with the development of HCC. Gene Ontology and pathway enrichment analysis of the differentially expressed genes revealed a strong disruption of the PI3K-AKT signaling pathway, which can be partially triggered by the extracellular matrix FN1. Conclusions: The IFNAR-1 promoter polymorphisms are not involved in the expression levels of the main IFNAR-1 transcript. The -77 VNTR has a regulatory role on the expression of a secondary, truncated, HCC-specific transcript, which in turn coincides with disruptions in cancer-associated pathways and in FN-1 expression modifications.